Programmed death-1+ T cells inhibit effector T cells at the pathological site of miliary tuberculosis. (24th November 2016) - Singh, A; Mohan, A; Dey, A B; Mitra, D K
Summary: Optimal T cell activation is vital for the successful resolution of microbial infections. Programmed death-1 (PD-1) is a key immune check-point receptor expressed by activated T cells. Aberrant/excessive inhibition mediated by PD-1 may impair host immunity to Mycobacterium tuberculosis infection, leading to disseminated disease such as miliary tuberculosis (MTB). PD-1 mediated inhibition of T cells in pulmonary tuberculosis and TB pleurisy is reported. However, their role in MTB, particularly at the pathological site, remains to be addressed. The objective of this study was to investigate the role of PD-1–PD-ligand 1 (PD-L1) in T cell responses at the pathological site from patients of TB pleurisy and MTB as clinical models of contained and disseminated forms of tuberculosis, respectively. We examined the expression and function of PD-1 and its ligands (PD-L1–PD-L2) on host immune cells among tuberculosis patients. Bronchoalveolar lavage-derived CD3 T cells in MTB expressed PD-1 (54·2 ± 27·4%, P  ≥ 0·0009) with significantly higher PD-1 ligand-positive T cells (PD-L1: 19·8 ± 11·8%; P  ≥ 0·019, PD-L2: 12·6 ± 6·2%; P  ≥ 0·023), CD19 + B cells (PD-L1: 14·4 ± 10·4%; P  ≥ 0·042, PD-L2: 2·6 ± 1·43%; not significant) and CD14 + monocytes (PD-L1: 40·2 ± 20·1%; P  ≥ 0·047, PD-L2: 22·4 ± 15·6%; P  ≥ 0·032) compared with peripheral blood (PB) of MTB and healthy controls. The expression of PD-1 was associated with a diminished number of cells producing effector cytokines interferon (IFN)-γ, tumour necrosis factor (TNF)-α, interleukin (IL)−2 and elevated apoptosis. Locally accumulated T cells were predominantly PD-1 + –PD-L1 +, and blocking this pathway restores the protective T cell response. We conclude that M. tuberculosis exploits the PD-1 pathway to evade the host immune response by altering the T helper type 1 (Th1) and Th2 balance at the pathological site of MTB, thereby favouring disease dissemination. Graphical Abstract: